The influence of age and water polo crawl techniques on heart rate in water polo players - Scurati, R.; Invernizzi, P. L.; Michielon, G.; Longo, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The swimming techniques adopted by water polo players usually do not reflect the classic swimming techniques. Additionally this sport is a highly energy demanding activity (1,2). Therefore heart rate, that reflects energy demand, may be different when measured during crawl or some of its water polo adaptations. For this reason attention is given to improve these adaptations during water polo training sessions; however these techniques could elicit different responses in terms of heart rate. PURPOSE. The purpose of this study was to look at the influence of age and water polo crawl techniques on heart rate in water polo (WP) players. MATERIAL AND METHODS. Ten under 20 (U20, mean±SD, age 18.2±0.4 years, height 176±7 cm, body mass 73.1±12 kg) and ten under 13 (U13, mean±SD, age 11.8±0.4 years, height 154±9 cm, body mass 48.5±8.6 kg) WP swimmers volunteered for this study. Each participant performed four 25m trials at a constant speed of 1m/s in four different crawl techniques used in WP: crawl (C), crawl head up (CU), crawl head up with ball between arms (CA), crawl head up pushing a ball (CP). Heart rate (HR) was monitored during each trial with a Polar® Team System heart rate monitor and used for further analysed. RESULTS. Between groups: HR was significantly lower in U20 than U13 for all four techniques (C: 104±13 vs 122±11 bpm p<0.05; CU: 117±13 vs 132±13 bpm p<0.05; CA: 123±9 vs 137±8 bpm p<0.05; CP: 125±8 vs 145±10 bpm p<0.05; U20 and U13 respectively). Within each group, for U20 HR values were 104±13 (C), 117±13 (CU), 123±9 (CA) and 125±8 (CP) bpm and have been found to significantly differ between each other (p<0.05) except for CA and CP (p>0.05). For U13 HR values were 122±11 (C), 132±13 (CU), 137±8 (CA) and 145±10 (CP) bpm and have been found to be significantly different between each other (p<0.05) except for CU and CA (p>0.05). CONCLUSIONS. The between groups comparison showed that age affects HR in the four different stroke techniques analysed, revealing that young WP swimmers spend more energy than the older ones in spite of the technique used. The within group comparison pointed out that the differences between each technique may be related to the age and the specificity of training in the two groups. U13 matches are characterised by static positions and ball control therefore this could be the explanation why we did not find any differences between CU and CA. On the other hand U20 matches due to their higher performance level are characterised by rapid movements of the players and the ball (pushing and throwing), thus the training focuses on more specific WP techniques, possibly explaining the lack of differences between CA and CP.